A novel strain of Yarrowia lipolytica as a platform for value-added product synthesis from glycerol. Issue 1 (December 2016) - Mirończuk, Aleksandra; Rzechonek, Dorota; Biegalska, Anna; Rakicka, Magdalena; Dobrowolski, Adam
Abstract Background Increasing interest of non-conventional yeasts has been observed for many years due to their biochemical characteristics and potential applications. Well-studied, oleaginous yeastY. lipolytica is an attractive host for converting a low-cost glycerol, into value-added products such as erythritol (sweetener) or citric acid. Glycerol is an important renewable feedstock and is the main co-product of biodiesel production, which is nowadays applied on a large commercial scale. To this end, we engineered the yeastY. lipolytica to increase the productivity of this strain. Results In this light, we enhanced glycerol assimilation by over-expression of theYALI0F00484g gene encoding glycerol kinase (GK) and geneYALI0B02948g encoding glycerol-3-P dehydrogenase (GDH). The modified strains have been tested for glycerol consumption rate and erythritol and citric acid synthesis under various conditions. Here, we show that the overexpression of GK and GDH, increased glycerol consumption resulting in rapid erythritol and citric acid synthesis. Next, we combined the two genes in the tandem gene construct for the simultaneous co-expression of GK and GDH, which further increased the desired product synthesis. The glycerol consumption was explored in a 5-L bioreactor and the engineered strains were able to utilize 150 g/L glycerol within 44–48 hours. The erythritol productivity for GK overexpression and co-expression of GK and DGH was 24 and 35 %, respectively, over the control strain. Moreover, we established conditions for the production of citric acid at pH 3.0, the engineered strains increased citric acid production 14-fold over the control. Conclusion This work demonstrates the excellent capacity of the engineered strains as a starting platform for further modification for broad-range value-added product biosynthesis from glycerol. This study presents the highest reported titer citric acid at low pH to date. The process parameters such as productivity and yield of erythritol and citric acid were significantly elevated, what is valuable for industrial applications.